(untitled) (Research, Society and Development, 2020)
In this article, the objective is to measure and evaluate noise levels at three public transport terminals on the Anhanguera axis line, in the city of Goiânia, Goiás, namely: the Padre Pelágio terminal, Praça A and Praça da Bíblia based on the values established by the Brazilian Standard NBR 10151/2019. Measurements were performed using two types of decibelimeters, between the months of August and November 2017, in the morning and afternoon, totaling three days a week for each terminal. The noise levels measured at the terminals were higher than the limits established by NBR 10151/2019, presenting values above 60 dB (A). It is concluded, therefore, that the noise levels detected in these terminals, averaging over 80 dB (A), can negatively influence the health of the people who work, circulate or use this public equipment and that, depending on the exposure time, can lead to public health problems.